Transparency Analysis of Information Transparency In Procurement of Goods/Services Through The Media Website (E-Procurement) in Realizing Goods Governance in Polewali Mandar Regency - Miswar, M; Karnay, Sudirman; Fatimah, Jeanny Maria (Universitas Muhammadiyah Surakarta, 2022)
Procurement of goods/services the government has an important role in the implementation of national development to improvement public services and development of the national and regional economy. EProcurement is a very good approach in an effort to realize a governance that is free from corruption, collusion and nepotism. The study was conducted to analyze: (1) How is the quality of information procuremnet of goods/services through the media website (e-procurement) in Polewali Mandar Regency; (2) How is the transparency of the procurement of goods/services through the media website (e-procurement) in Polewali Mandar Regency. Descriptive qualitative research method, conducted using data from various selected informants using purposive sampling technique with the number of informants as many as 5 (five) people. The results showed that the quality of information on the procurement of goods/services through the media website (e-procurement) in Polewali Mandar Regency was seen from four indicators, namely accurat;, timel line; relevant; and complete, including quality. The transparency of the procurement of goods/services through the media website (e-procurment) in Polewali Mandar Regency was seen from four indicators namely ease of access, feedback mechanism, update infornation, and ease of site including being transparent.